Molecular characterization of proteolytic bacteria associated with Malaria vectors: Anopheles sundaicus and Anopheles vagus - Senjarini, Kartika; Labes, Antje; Wathon, Syubbanul; Oktarianti, Rike; Raras, Tri Yudani Mardining; Ardyah, Naura Paramitha Cindy; Agustin, Dita Paramytha; Ainiyah, Durotun; Utami, Diah Ayu (Faculty of Medicine, Universitas Trisakti, 2024)
BACKGROUNDAnopheles (An.) sp. transmits Plasmodium parasites that cause malaria. In its life cycle in the mosquito’s body, Plasmodium passes through 2 mosquito organs, namely the salivary glands and midgut. The bacterial community (symbiont bacteria) in these organs has been known to influence and/or inhibit the development of the Plasmodium life cycle by producing specific proteases. This research aims to isolate and characterize symbiotic bacteria with proteolytic activity from 2 important malaria vectors in Indonesia: An. sundaicus and An. vagus. METHODSA total of 183 bacterial originating from the salivary glands and midgut were successfully isolated. Initial screening was carried out based on morphological differences, followed by purification of the selected isolates to obtain single colonies. The selected isolates were then subjected to an initial proteolytic ability test using skim milk agar media. Only isolates with proteolytic activity were further characterized with the 16SrDNA molecular marker. The isolates were pabs5 from the salivary glands and pabs3 from the midgut of An. vagus, while pdbs3 and ecbs4 were isolates from the salivary glands and midgut of An. sundaicus. RESULTSMorphological and molecular characterization showed that both pabs5 and pabs3 isolates were Pseudomonas(Ps.) aeruginosa, while ecbs4 was Enterobacter cloacae and pdbs3 was Pantoea dispersa. These species werefirst discovered in Anopheles vagus and Anopheles sundaicus. CONCLUSIONThe ability of Ps. aeruginosa and Pantoea dispersa to produce proteases indicated their potential role in the exploration of new strategies to control mosquito vectors that transmit pathogens.